Metodologia de la investigacion aplicada a la asociacion frijol- maiz - Davis, J.H.C. (International Center for Tropical Agriculture, 1983)
Three trials were carried out at CIAT-Palmira to quantify the effect of plot edges and useful plot size in beans. In the 1st trial (sown in Oct. 1977), the competition effect of 36 climbing bean var. associated with maize ICA H-210 in adjacent plots and the effect of the alleys on plot edges were studied. The harvested plot area was directly proportional to the F test value for var. effect, and inversely proportional to C.V. The effect of lateral edges was not significant. The effect of headland edges for 2 and 4 seed beds was influenced by the var. Light utilization was different in all the var. Yields of most productive bean var. were less overstimated when headland edges were included. The 2nd trial was sown with 3 replications, using climbing bean var. P589 and maize ICA H-207. The 3rd trial had 4 replications with the same bean var. associated with maize ICA H-210. Results of the 2nd trial show a min. effect of 2-m edges, with a greater effect for the association than for the monocrops. Beans in association acted as an anchorage to maize, thus reducing lodging. It is concluded that there was no need to leave lateral edges between plots, since there was not a significant competition effect between adjacent plots. A marked effect of headland edges was observed, not uniform for all the var. A useful plot of 11 square meters is required for climbing bean associated with maize, to detect a significant 24 percent difference over the mean, with 4 replications. Various quantification methods of the association system as a whole and regarding each component in monoculture are described and compared. Tables and figures illustrating exptl. results are included. (CIAT)